Simultaneous Determination by Gas Chromatography of Lindane and Carbaryl in Combined Formulations - Indrajit Sen; Ajay Shandil; Manjeet Aggarwal; Rakesh Kumar Khandal (E-Journal of Chemistry)
A gas chromatographic method developed and validated for simultaneous determination of lindane and carbaryl for quality evaluation of lindane-carbaryl granule, using a glass capillary HP5 column (30 m x 0.32 mm; 0.25 μm), temperature programming with flame ionization detector and dibutylphthalate as an internal standard. The calibration graphs were found linear in the concentration range of 1 μg/mL to 1000 μg/mL for both lindane and carbaryl with correlation coefficient of 0.999 and 0.999 respectively and co-efficient of variation for intra-day and inter-day repeatability studies at different concentration levels was found to be less than 2%. The accuracy of method ranges between 98.5% to 100.8%. Specificity and robustness were also within the acceptable range. The method is highly sensitive with LOD and LOQ as 0.5 and 2 μg/mL for lindane and carbaryl respectively. The method has been tried on several formulations of lindane-carbaryl granules for quality control and has been found to be applicable.